2019
DOI: 10.2355/isijinternational.isijint-2018-515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-temperature Nitridation on Sulfide Stress Corrosion of 321 Austenitic Stainless Steel in H<sub>2</sub>S-Containing Environments

Abstract: The effect of low-temperature nitridation on corrosion resistance and sulfide stress corrosion (SSC) behavior of 321 austenitic stainless steel in H 2 S-containing environments was investigated. Varying fourpoint bend loading of 80 pct yield stress, 100 pct yield stress, 120 pct yield stress were respectively applied to nitrided 321 austenitic stainless steels. Although no macroscopic corrosion cracking is observed, pits are formed on the alloy surfaces. As the bending stress increases, the numbers and depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The contributions include FeS (160.48 or 160.8 eV), FeS 2 (161.68 or 162.2 eV), S (163.1 or 163.6 eV), and FeSO 4 (168.4 eV). [ 26–33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions include FeS (160.48 or 160.8 eV), FeS 2 (161.68 or 162.2 eV), S (163.1 or 163.6 eV), and FeSO 4 (168.4 eV). [ 26–33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The contributions include FeS (160.48 or 160.8 eV), FeS 2 (161.68 or 162.2 eV), S (163.1 or 163.6 eV), and FeSO 4 (168.4 eV). [26][27][28][29][30][31][32][33] The XRD spectra revealed that sulfide was present as Fe 1−x S, while the XPS analysis detected sulfide peaks as FeS and FeS 2 . This may initially appear to be contradictory, but it is not.…”
Section: Analysis Of Corrosion Product Componentsmentioning
confidence: 99%
“…Stainless steels are widely utilized for nuclear engineering structural components because of their excellent corrosion resistance, weldability, and mechanical properties. [12][13][14] In the pressurized water reactor nuclear power plant, the nuclear island is regarded as the most important part; it is basically composed of pressure vessel, primary circuit main pipe, pressurizer, and main coolant pump, which are primarily linked by stainless steel components. In third generation AP1000 nuclear reactors, 316LN austenitic stainless steel is typically used as a material for the primary circuit main pipe.…”
Section: Introductionmentioning
confidence: 99%